REE VARIATIONS ACROSS THE PENINSULAR RANGES BATHOLITH: IMPLICATIONS FOR BATHOLITHIC PETROGENESIS AND CRUSTAL GROWTH IN MAGMATIC ARCS - Gromet Peter; Silver Leon T. (My University, 1987)
Rare earth element (REE) patterns of plutonic rocks across the Cretaceous Peninsular Ranges batholith vary systematically west to east, transverse to its long axis and structural trends and generally parallel to asymmetries in petrologic, geochronologic and isotopic properties. The batholith can be ivided into three distinct parallel longitudinal regions, each defined by distinct REE pattern types. An abrupt transition occurs between rocks with slightly fractionated REE patterns in the western (coastal) region and rocks with middle to heavy REE fractionated and depleted patterns in the central region. Further to the east a second transition to strongly light REE enriched rocks occurs. The slopes of the REE patterns within each of these regions are largely independent of rock type. The first REE transition is closely coupled to regional discontinuities in other parameters: elimination of negative Eu anomalies, an increase in Sr content, and a marked restriction in petrologic diversity. This transition occurs over a range of initial 87Sr/86Sr ratios and ?18O values, but approximately correlates to a major shift in the emplacement style of the batholith from a stationary arc to a rapidly eastward-migrating (cratonward) arc. The sense of the regionally consistent REE trends cannot be explained by crystallization, assimilation, combined crystallization-assimilation, or mixing processes. The consequences of assimilation and high-level differentiation are not observed generally, despite the sensitivity of the REE to these processes. Geochemical and petrological features argue that the partial melting of mafic source rocks in which plagioclase-rich (gabbroic) residual assemblages abruptly gave way laterally and downward to garnet-bearing (eclogitic) residual assemblages produced all the changes associated with the first REE transition. The change in residual assemblages from gabbroic to eclogitic was superimposed on source regions already zoned in light REE abundances, 87Sr/86Sr and 18O. Temperature and pressure constraints on the source regions place them in a subcrustal location. The calcic nature of the batholith and the dominance of tonalite and low-K2O granodiorite in all its regions argue that the source materials are broadly basaltic in composition. Experimental studies are consistent with the generation of the abundant tonalitic magmas by the partial melting of basalt under both low and high pressure conditions. Arc basalts such as those commonly erupted in modern island arcs and continental margins are inferred to have provided much of the source material and the heat. Additional high-18O components are needed in the more easterly source regions. These materials must be distributed so as to contribute equally to the range of magmas that occur in a given local region, and must preserve the calcic nature of batholithic sources. Altered basalts of ancient oceanic crust and possibly their associated metasediments, previously incorporated into the lithosphere beneath the continental margin during earlier cycles of subduction, most readily satisfy these constraints. The REE geochemistry of the central and eastern regions of the batholith differs from that of oceanic island arcs in the presence of strongly heavy REE depleted and fractionated magmas. A model is proposed in which arc basalts accumulate beneath a crustal layer. Melting of accumulated material at low pressure produces magmas of the western region. Where thickening of the basaltic underplate is sufficient to form eclogitic assemblages, eclogite-derived magmas of the central and eastern region are produced. The abrupt transition to eclogite-derived magmas that suggests a process driven by a density instability is responsible for their origin. The Peninsular Ranges batholith appears to be representative of a major differentiation process in which mantle-derived basalt is remelted, contributing its more sialic fractions to the continental crust and leaving its mafic to ultramafic residues in the mantle. This process preserves the sialic character of the continental crust and may play a significant role in its growth and evolution. The batholith and the processes that produced it may be a more appropriate basis than immature oceanic island arcs on which to construct models of continental growth and evolution.
Keywords: Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая